The WTO in the twenty-first century dispute settlement, negotiations, and regionalism in Asia - Taniguchi, Yasuhei; Yanovich, Alan; Bohanes, Jan (Cambridge University Press, 2007)
Leading scholars and international trade practitioners examine the significant issues facing the WTO.